Evaluation of the Effect of Dissolution Conditions on the Release Profiles of Felodipine from the Extended Release Push-Pull Osmotic Tablets - Vu, Thi Thanh Huyen (H. : ĐHQGHN, 2020)
The bilayered push–pull osmotic tablets of 5 mg felodipine were prepared by the double compression method, then the core tablets were coated with cellulose acetate as a semipermeable membrane. One releasing orifice was drilled by laser on the drug side of tablets. The osmotic tablets of felodipine containing low molecular weight PEO (200.000) as the primary component in the drug layer, high molecular weight PEO (5.000.000) as a swelling agent in the push layer and natri chloride as osmotic agent in both drug and push layers which were semi-permeable membrane coated with a weight gain of 8.5 % and the drilled release oriﬁce of 0.8 mm. The influence of dissolution conditions on the release profiles of felodipine from the extended release push-pull osmotic tablets was studied. Dissolution studies of the osmotic tablets of felodipine were carried out in dissolution media with different media pH, stirring speeds or osmotic pressures. The results of the study showed that the drug release profile was similar in dissolution media containing surfactant mimics the in vivo state with varying pH and stirring speeds. However, felodipine released from the osmotic tablets was inversely proportional to the osmotic pressure of the dissolution medium. Therefore, the drug release rate from the osmotic tablets was independent of media pH and stirring speeds, but dependent on the osmotic pressure of the dissolution medium.